Estudo dos mecanismos associados à disfunção cognitiva em modelo murino de malária cerebral - Aline Silva de Miranda (2015)
Malaria is the main and most serious parasitic disease of mankind. Cerebral Malaria (CM) has been defined as a potentially reversible diffuse encephalopathy characterized mainly by coma and the presence of asexual forms of P. falciparum parasites in peripheral blood smears in the absence of other causes of encephalopathy. This condition presents a complex and incompletely understood pathogenesis, in which vascular, immunological and metabolic changes have been described. The mortality rate is high and 10 to 20% those who survived remain with cognitive and behavioral deficits even after a successful resolution of infection by antimalarial compounds. In this scenario, studies to investigate the cellular and molecular mechanisms underlying CM pathogenesis as well as the efficacy of adjunctive therapies in improve CM outcome are urgently warranted. In the present study, using the Plasmodium berghei ANKA (PbA) model of CM, we demonstrated that the enhancement in inflammatory cytokines (IL-6, IFN- e TNF-) and chemokine (CCL11) levels in the hippocampus influenced neurotrophic factors expression reducing neurogenesis and inducing cell death in this region contributing to the cognitive impairment observed during the acute phase of infection. A single dose of the antimalarial artesunate (32mg/kg) was able to significant attenuate the production of inflammatory cytokines in the hippocampus and frontal cortex on day 5 post-infection promoting a significant improve of survival and CM clinical signs. Furthermore, MK801 (0.5mg/kg), a non-competitive NMDA receptors antagonist, prevented cognitive and behavioral impairment following infection resolution by the antimalarial chloroquine (30mg/kg). Additionally, MK801 was also able to modulate the TH1/TH2 inflammatory response and to induce neurotrophic factors release in the hippocampus and frontal cortex exerting a neuroprotective effect. The current study provided further evidence regarding inflammatory mediators role in regulating neurogenesis and cell death in the hippocampus during the acute phase of CM, contributing significantly for cognitive deficits development. Cognitive and behavioral sequelae following infection resolution depends on immune and neurotransmitter system interactions indicating that interventions targeted modulation of the glutamatergic system may constitute potential therapeutic adjuvants to antimalarial treatment.